Attenuation of Ischemia-Reperfusion Injury and Improvement of Survival in Recipients of Steatotic Rat Livers Using CD47 Monoclonal Antibody. Issue 7 (July 2016) - Xiao, Zhenyu; Banan, Babak; Xu, Min; Jia, Jianluo; Manning, Pamela T.; Hiebsch, Ronald R.; Gunasekaran, Muthukumar; Upadhya, Gundumi A.; Frazier, William A.; Mohanakumar, Thalachallour; Lin, Yiing; Chapman, William C.
Abstract : Background: Despite the efficacy of orthotopic liver transplantation in the treatment of end-stage liver diseases, its therapeutic utility is severely limited by the availability of donor organs. The ability to rehabilitate marginal organs, such as steatotic allografts, has the potential to address some of the supply limitations of available organs for transplantation. Steatotic livers are more susceptible to ischemia-reperfusion injury (IRI), which is exacerbated by the thrombospondin-1/CD47 pathway through inhibition of nitric oxide signaling. We postulated that CD47 blockade with a monoclonal antibody specific to CD47, clone 400 (CD47mAb400) may reduce the extent of IRI in steatotic liver allografts. Methods: Orthotopic liver transplantation was performed using steatotic liver grafts from Zucker rats transplanted into lean recipients. Control IgG or the CD47mAb400 was administered to the donor livers at procurement. Serum transaminases, histological changes, and animal survival were assessed. Hepatocellular damage, oxidative and nitrosative stress, and inflammation were also quantified. Results: Administration of CD47mAb400 to donor livers increased recipient survival and resulted in significant reduction of serum transaminases, bilirubin, triphosphate nick-end labeling staining, caspase-3 activity, oxidative and nitrosative stresses, and proinflammatory cytokine expression of TNF-α, IL-6 and IL-1β. Conclusions: We conclude that administration of CD47mAb400 to donor grafts may reduce IRI through CD47 blockade to result in improved function of steatotic liver allografts and increased survival of recipients and represent a novel strategy to allow the use of livers with higher levels of steatosis. Abstract : Investigation into therapeutic role of CD47 antibody on attenuation of fatty liver graft injury in a rat orthotopic liver transplantation model. CD47 blockade significantly improves the fatty liver graft function and increases survival through inhibition of proinflammatory signaling.